An Alternative Method for Measuring Employment Quality in Colombia (2008–2012) - Jiménez Restrepo, Diana Marcela; Páez Cortés, Jessica Natalia (Sociedad y Economía, 2014)
Although we do not have an exclusive definition about employment quality, we do agreethat it must meet minimal conditions such as the existence of a contract, the access tosocial security, a fair wage, and a fair workday. For the main 13 metropolitan areas ofColombia, having available data for the second quarters from 2008 to 2012, and applyingthe multiple factor analysis, as a technique making part of an alternative methodologyfor measuring job quality, we found that many employees earn at least one minimumwage, they don’t have a contract, their workday is not legal, and they are affiliated tohealth service.